Toxicological assessment of Euglena gracilis strain Eu029 shows no adverse effects in vivo and in vitro. (6th March 2018) - Symonds, Jennifer M; Beauchamp, Nicole; Takeuchi, Takuto; Yamada, Koji; Atsuji, Kohei; Asayama, Yuta; Suzuki, Kengo; Kruger, Claire L
Euglena gracilis is a single-celled organism capable of photosynthesis and heterotrophy. Euglena sp. have long been studied in the laboratory for its metabolic pathways, cell motility, and ease of culture. The safety of E. gracilis strain eu029 (EG029) for use as a food ingredient was assessed in a bacterial reverse mutagenesis assay (Ames), rec assay, in vivo micronucleus assay, acute toxicity study in mice, 13-week toxicology in rats, and a teratology study in mice and rats. EG029 was not genotoxic. The No Observed Adverse Effect Level (NOAEL) in the 13-week study was greater than 1000 mg/kg/day, the highest dose tested. Teratogenicity studies did not find any defects in fetal development or effects to maternal health in rats at 1000 mg/kg/day, the highest dose tested.